Alfabetização científica de alunos do ensino superior frente às implicações da engenharia genética e a idealização do "melhoramento humano" - Schneider, Eduarda Maria (2015)
In the present scenario of scientific and technological development, one of the areas of Science that stands out due to its accelerated production of knowledge is the genetic engineering, referring to the set of techniques that involves the manipulation of genetic material. However, applications of these new techniques, which promise the solution of problems related to the human species, must be analyzed carefully, since it may correspond to a dangerous ideology, based on unethical principles, as occurred in the eugenics movement of the late nineteenth and early twentieth century. Eugenics, which aimed to improve the human species, became a racist and discriminatory character movement. Recognizing the similarities between the advances in human genetic engineering and the ideology of eugenics movement, it is important to study possibilities of entering discussions of these topics in different levels of education and ascertain how this approach has been made for the formation of critical and participating citizens in social decisions. In this context, the objective of this research was to build, validate and implement a research instrument of knowledge, values and practices presented by higher education students about genetic engineering and idealization of "human enhancement". The survey was conducted with university initial and final year courses in biological areas and humanities at a university located in Brazil and another in Portugal. The methodology of elaboration, validation and instrument analysis followed a quantitative approach based on the Likert scale, statistical tests such as Alpha, KMO and Bartlett and principal component analysis (PCA), the frequency of the means and correlations component, calculated with the help of Statistical Packet for Social Sciences (SPSS). Regarding the questionnaire validation, the applied statistical tests showed good results of semantic and statistical reliability, being valid as a research tool. The ACP resulted in three main components with factor loadings similar to Brazil's dataset and Portugal, which were classified respectively as values, practices and knowledge, demonstrating the validity of the components and the KVP model to analyze views on the subject investigated. The results of frequency and average component I indicated that most of the surveyed students show deterministic values as to the use of genetic engineering for the improvement of the human population, and their improvement as regards diseases. However, most scholars of the two areas surveyed in both countries, shows systemic values regarding the use of this technology to seek the improvement of physical and intellectual characteristics. In the analysis of the frequencies and component averages II found that the majority in both the biological group of students, such as in the humanistic one, in both countries, provides consistent answers with practices contrary to the eugenics movement ideologies. Regarding the component analysis III, we find out that most of the respondents in both countries demonstrated to know the biosafety laws and the complexity of interactions between genetic inheritance, environmental and development of the body, but do not hold knowledge about the term eugenics and are skeptical or unaware of the possibility of sex selection and the selection of healthy embryos. Overall, the results achieved demonstrate the validity of the instrument and this type of research for the investigation of knowledge, values and practices of genetics and eugenics engineering, revealing the need for training that integrates these three centers to provide scientific literacy of the population.